2022
DOI: 10.30574/gscbps.2022.18.3.0072
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical and microbiological assessment of drinking water quality in Swakin city

Abstract: The study was carried out on water samples collected from different sites in Swakin City and Arbat area in Sudan. Five samples were collected during two seasons (winter and summer) to determine the quality of the drinking water by looking into physicochemical and microbial aspect. Results showed that some samples exceeded the Sudanese and international standards in turbidity and some samples showed the presence of coliform, E. coli and faecal streptococcus bacteria. It is recommended to carry out microbial exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 3 publications
0
1
0
Order By: Relevance
“…Temperature affected the physicochemical parameters of sludge samples, so it is considered as a key factor in shaping the structures of microbial populations. High records of microbial loads of S3 sample are harmonious with the results of Madni et al [35] who reported that high temperature favors the survival of microorganisms. The global energy crisis and the limited resources necessitates the search for alternative sustainable energy sources.…”
Section: Discussionsupporting
confidence: 85%
“…Temperature affected the physicochemical parameters of sludge samples, so it is considered as a key factor in shaping the structures of microbial populations. High records of microbial loads of S3 sample are harmonious with the results of Madni et al [35] who reported that high temperature favors the survival of microorganisms. The global energy crisis and the limited resources necessitates the search for alternative sustainable energy sources.…”
Section: Discussionsupporting
confidence: 85%
“…Similar results observed in Nigeria that the microbial load after 24 hours and 48 hours of incubation, with the values 1.8×10 5 CFU/ml and 2.6×10 5 CFU/ml respectively, which is also higher than the recommended value (Sunday et al, 2014). Additionally, Madni et al (2022) found the microbial load 6.5×10 3 to 8.9 × 10 5 during winter and 5.5×10 3 to 7.3×10 5 during summer season in Swakin city, Sudan. According to guideline of WHO (1996), TVC value should be 1×10 3 CFU/ml.…”
Section: Resultsmentioning
confidence: 86%